Evaluasi Kritis Ritual Sangiang Dalam Perspektif Kristiani di Paroki Santo Fransiskus Assisi Parenggean - Aldous Fernandes; Alexsander Vale; Dency Elzahra, (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
This research aims to find out how the Dayak Ngaju Catholic community views the Sangiang ritual, how the Ngaju Dayak Catholic community appreciates the sacrament of anointing the sick and the implementation of the sacrament of anointing. ? in Ngaju Dayak culture. So. The method used in this research is a qualitative research method. Data was collected through interviews, observations and notes. The data obtained was analyzed following the steps of Miles and Huberman, namely reducing data, presenting data, and drawing conclusions. The results of the research show that the Ngaju Dayak people recognize the sangiang ritual as a healing ritual in their culture. And people know that the sacrament of Anointing of the Sick in the Catholic Church is one of the sacraments that prays for sick people to be given strength so they can overcome all illnesses with God's help. This conclusion shows that the sangiang ritual has a socially oriented dimension and makes people aware that living together requires a sense of mutual care. The values contained in the Sangiang ritual are the values of community and brotherhood. The presence of the Church in this culture is the starting point for proclaiming the Kingdom of God, especially by ensuring that the catechism is linked to the sacrament of the Anointing of the Sick, because it is God who acts for healing, especially during the sangang ceremony.